Biomechanical measurements of human impacts in basketball - Halkon, B.; Mitchell, S.; Payne, T.; Carbo, J. (Procedia Engineering, 2014)
Despite significant advances in materials and manufacturing techniques applied to sports protective equipment in recent years, sports injuries due to impact, contusions in particular, continue to occur. In this paper, a test methodology aimed at collecting data from laboratory-simulated human-on-human impacts in Basketball is presented. The study was executed in three stages with data being collected from: i) human on instrumented bag; ii) impactor on instrumented bag and iii) impactor on instrumented human impacts. In all cases, high-speed video and/or kinematic motion data capture systems were used to obtain parameters such as inbound/outbound velocities, contact durations while resistive ink technology pressure sensing films were used to estimate parameters such as pressure distributions, peak pressures, contact areas, impact forces. Elite-level athletes were used in all human trials to ensure that impact techniques and levels representative of the elite game were obtained and that tolerance to impacts was similarly representative. Two common strikes were simulated: knee on thigh and elbow on rib/torso. Five participants were used to collect the human-on-bag data while 12 participants were used to collect the impactor-on-human data. Between three and five impacts per scenario were performed to enable noise averaging and, importantly, likely injury- causing outlier capture.